Commuters' effect on local labour markets: A german case study - Giovanni Russo; Peter Nijkamp; Aura Reggiani; Federico Tedeschi (European Regional Science Association (ERSA), 2010)
This paper offers an exploratory investigation of the effects of inbound commuter flows on employment in regional labour markets in Germany. For this purpose, we distinguish three channels that could transmit the effects concerned: a crowding-out mechanism, and two labour demand effects (the first is an aggregate demand effect, while the second is a positive externality on vacancy creation). To this end, we develop a stepwise commuting impact model. Our results bring to light that, on the whole, commuter flows have a positive and robust effect on both employment and the number of jobs in the receiving labour market districts, but a distinctly negative effect on the share of jobs filled by resident workers. We then interpret the implications of our results, and, finally, we suggest ways in which the analysis could be improved and expanded.
Keywords: 330